Sistem Informasi Linen Management Berbasis RFID Menggunakan RESTFul Web Service (STUDI KASUS : PT. INDO DHARMA BERLIAN) - Farkhan Azmi; Widhy Hayuhardika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
PT. Indo Dharma Berlian is a company engaged in the field of Convection, General Suppliers, and National scale construction services. PT. Indo Dharma Berlian cooperates with PT. Cardig Aero Service Group (CAS). PT. CAS itself has several business segments, one of which is the CAS Facility. One of the clients who take advantage of the CAS Facility service is Siloam Hospital. In their business processes, the three companies interact with each other. Previously the interaction between the three parties in the company was only based on a pass. Sometimes the amount of linen that comes out is not the same as the incoming linen because there is no support system for linen management. Therefore, researchers conducted research with the aim of developing a mobile-based linen management application and a website that provides services in recording linen transactions using RFID (Radio Frequency Identification) based technology. This application will later become a substitute for linen management before there is an application. So that it requires hospital employees to perform an RFID scan on the linen containing the linen id then the laundry employees validate the linens that have been input on the system, and vice versa from the laundry to the hospital. In the requirements analysis stage, there are nineteen functional requirements for web and mobile systems. Mobile Apps are built with Android Studio using the java programming language and using the SDK from the C72 chainway. Web Apps are built with the YII (Yes, it Is) framework using the PHP programming language. In testing, system functionality uses validation testing to users for all system functions, the results are 100% valid.